Penurunan Kadar COD Pada Limbah Cair Hotel Dengan Sistem Moving Bed Biofilm Reactor (MBBR) Menggunakan Chlorella sp. - Mustika Chairani; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Organic matter contained in the hotel wastewater can be used as a nutrients of microalgae Chlorella sp. so its reduce COD. There are two treatment process happened in MBBR, suspended growth and attached growth by adding biocarriers in the reactor as a place for the propagation of microalgae. This research describes the study of effect of biocarrier (Kaldnes 1 (K1)) filling volume to decreasing COD in hotel wastewater. The study conducted in batches by varying of Kaldnes 1 (K1) filling volume with 4 different levels, that is 0% (without the addition of Kaldnes 1 (K1)), Kaldnes 1 (K1) filling volume as many as 10%, 20%, and 30% (wastewater volume). This process takes up to 5 days with solar irradiation in the MBBR. The result showed that 20% Kaldnes 1 (K1) filling volume happened in days-5 was able to reduce COD with efficiency of COD is 81.82%.Keyword: Chlorella sp., MBBR, Hotel Wastewater, COD